PENGARUH HEDONIC SHOPPING DAN SHOPPING LIFESTYLE TERHADAP IMPULSIVE BUYING MELALUI POSITIVE EMOTION PADA KONSUMEN PENGGUNA E-COMMERCE SHOPEE DI KOTA PEKANBARU - Mariska Zizia; Taufiqurrahman Taufiqurrahman; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study is to explain what the influence of Hedonic Shoppingand Shopping Lifestyle on Impulsive Buying with Positive Emotion as a interveningvariable on Shopee E-commerce users in Pekanbaru City. Someone’s hedonic factorcoupled with changes in people's lifestyles assisted by the presence of online stores, willcreate positive feelings and increasingly influence them to make unplanned purchases.This study uses a quantitative approach with a survey method. The sample in this studywas 119 consumers using Shopee E-commerce in Pekanbaru City on condition that theyhad made shopping transactions at Shopee E-commerce 10 times in the last 6 months.Sampling used non-probability sampling method and accidental sampling technique. Theresearch instrument used a questionnaire and analyzed using Path Analysis.The results ofthis study indicate that both Hedonic Shopping and Shopping Lifestyle have a positiveand significant effect on Positive Emotion. Likewise, Positive Emotion has a positive andsignificant effect on Impulsive Buying. Furthermore, it is known that Hedonic shoppingand Shopping Lifestyle have a positive and significant effect on Impulsive Buying throughPositive Emotion on Shopee E-commerce users in Pekanbaru City. Keywords: Hedonic Shopping; Shopping Lifestyle; Positive Emotion; Impulsive Buyingand E-commere Shopee